The relationship between sports specialization and mental toughness - Buhrow, C.; Digmann, J.; Waldron, J. J. (International Journal of Exercise Science, 2016)
The pros and cons of early sport specialization compared to diversification have been examined in many research studies. The purpose of this study was to determine (a) the relationship between mental toughness and age of specialization in sport, and (b) differences in mental toughness based on early specialization of sport and gender. College athletes (N = 102) completed surveys about specialization and mental toughness, including MeBTough. The mean age of specialization was 13.45 (± 4.47). Results showed no significant difference in mental toughness of those who specialized early and those who did not. There was no significant difference in mental toughness scores based on gender. It is possible that there were no differences in mental toughness based on early specialization because most of the athletes played multiple sports in high school and did not actually specialize until their later years of high school. Because the athletes in the study had similar sporting experience, it is possible that both men and women developed similar levels of mental toughness. Mental toughness develops over the years by maximizing athletes` opportunities and competition experiences, and athletes can develop their mental toughness by choosing to specialize or diversify in sports. More research needs to be done pertaining to sports like gymnastics and figure skating where early specialization may be critical to success.